Correlation and path analysis as an indirect selection criterion for sunflower achene productivity - Gonsiorkiewicz Rigon, Carlos Alberto; Gonsiorkiewicz Rigon, Joao Paulo [UNESP]; Capuani, Silvia [UNESP] (Univ Federal Uberlandia, 2014)
The study was conducted in two different locations in South Brazil, in tillage in the 2009/2010 season on eight sunflower hybrids, aiming to determine the path correlations and coefficients between primary and secondary characters on the main variable of achene productivity. The correlations were similar between environments. The characters of the head diameter and mass of a thousand achenes had a significant influence on sunflower productivity. Based on the magnitude of the direct and indirect effects, we highlighted all primary components on the main variable, beside the good determination coefficient and low residual effect. The secondary component, the number of achenes, despite the significant direct effect on productivity, was indirectly influenced by the primary components, making it an undesirable character for selection.

O estudo foi realizado em dois locais no Sul do Brasil na safra 2009/2010, por meio de oito híbridos de girassol, com o objetivo de determinar os coeficientes de correlações e a análise de trilha entre os caracteres primários e secundários sobre a variável principal produtividade de aquênios no girassol. As correlações foram semelhantes entre os ambientes, sendo o diâmetro do capítulo e massa de mil aquênios com maior influência significativa sobre a produtividade do girassol. Com base na magnitude dos efeitos diretos e indiretos, destacamos todos os componentes primários sobre a variável principal, além do coeficiente alto de determinação e efeito residual baixo. O componente secundário, o número de aquênios, apesar do efeito direto na produtividade, é influenciado indiretamente a partir dos componentes principais, tornando-se um carácter indesejável de seleção.
Correlação e análise de trilha como critério de seleção indireta para produtividade de aquênios de girassol
Keywords: Helianthus annuusL.; Components; Yield; Selection; Helianthus annus L.; Componentes; Rendimento; Seleção